Analisis Jalur Simplification Model Untuk Eksplorasi Penerimaan Aplikasi AI Sebagai Media Pembelajaran - Usmanur Dian Iswanti; Tri Lathif Mardi Suryanto; Doddy Ridwandono (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
The development of AI is having a significant impact on education. AI applications are designed to improve student understanding, but their implementation faces challenges that affect user acceptance. Initial research with the UTAUT2 model in public high schools showed that only hedonic motivation, habit, facilitating conditions, and behavioral intention had a significant influence on application acceptance and use. Therefore, this study will use a simplification model that focuses on significant variables, namely hedonic motivation (HM) and habit (H) on behavioral intention (BI), as well as facilitating conditions (FC), habit (H), and behavioral intention (BI) on use behavior (UB). This study is expected to provide in-depth insight into the important factors that influence the acceptance and use of AI applications in learning, as well as provide practical contributions to improve the implementation of learning technology in high schools.